A COMPARATIVE STUDY OF ENGLISH AND UZBEK LEGAL TERMS (Ustozlar uchun, 2025)
This article explores the similarities and differences between English and Uzbek legal terminology, focusing on their linguistic, cultural, and functional aspects. The study aims to identify the main factors influencing the formation and usage of legal terms in both languages, such as history, culture, and legal traditions. It also analyzes the challenges of translating legal terms from English into Uzbek and vice versa, emphasizing the importance of equivalence and accuracy in legal translation. The research highlights that while English legal terminology is deeply rooted in the Anglo-Saxon and Roman legal systems, Uzbek legal terminology has developed under the influence of Islamic law, Soviet legislation, and modern democratic reforms. Comparative analysis shows that despite linguistic differences, both systems share universal legal concepts reflecting justice, equality, and social order.